The Influence of Principal's Transformational Leadership and Work Motivation on Teacher Innovation at State Elementary Schools - Haestetika, Meeka; Marsidin, Sufyarma; Anisah; Sulastri (Journal of Education Reseach and Evaluation, 2023)
Teacher innovation is the ability of a teacher to be creative in managing the learning process with the competence they has. Based on the pre-survey in the field, it is illustrated that the innovation of public elementary school teachers is still low. This study aims to analyze the effect of the principal's transformational leadership, and work motivation on the innovation of public elementary school teachers. This research is a correlational quantitative research with associative type. The research instrument used a Likert Scale model questionnaire. The trial was carried out on a population outside the sample of 30 people.Then the research data were analyzed using the average score (Mean) for data description, requirements test, namely the normality test, homogeneity test, linearity test and multicollinearity test. Then test the hypothesis using simple linear regression and multiple linear regression testing using SPSS version 24.0. The results of the descriptive analysis of teacher innovation were 82.15%, the transformational leadership of school principals was 91.12%, and work motivation was 91.51%. The results of the data analysis show that there is a significant influence between the transformational leadership of school principals on teacher innovation by 17.4%, there is a significant effect between work motivation on teacher innovation by 33.5%, and there is a significant influence between the transformational leadership of school principals and work motivation together on teacher innovation by 35.3%.